IMPLEMENTASI PERJANJIAN PERBATASAN RI – RDTL DALAM UPAYA PENYELESAIAN MASALAH PERBATASAN (Studi Kasus di Kabupaten TTU – RI dengan Distrik Oecusse-RDTL) - KOLNE, YAKOBUS (Politika: Jurnal Ilmu Politik, 2014)
Recent observation regarding the reality of people’s living in the border region of the Republic of Indonesia-Timor Leste revealed the facts that they are still facing many problems directly related to all aspects of life that requires the government to take action through the implementation of the state border treaty policy in accordance with the community desire and expectation for sa conducive environment to the life of the nation and the state. The purpose of this study were: 1) to describe the implementation of border treaty between Indonesia and Timor Leste in the resolution of border problems in the District of Oecusse, TTU and 2) to describe and interpret the factors supporting and inhibiting the implementation of the border agreement in resolving the border issues. The method of this study was descriptive qualitative approach. The informants in this study were: Deputy Governor of NTT, TTU Regent, TTU Vice Regent, head of the BPP of TTU and Pamtas RI- Timor Leste Task Force, selected by purposive technique. The study found that: First; communication dimension: (a) lack of community involvement in determining national boundaries; (b) discussion/dialogue with the community had not been maximally conducted; (c) there is requirement to improve existing products of bilateral agreements. Second; Resources dimensions: (1) poor coordination between the senior government and the local government; (2) bolstering up to build further discussion/dialogue between the two countries involving indigenous people had not been done as proposed by the local government ; (3) lack of supporting infrastructures available for the people in the border region; (4) Minimum budget capacity. Third; Bureaucratic structures: (1) lack of supervision for the institutions/implementing agencies; (2) officials in the senior level of government did not involve the Government in the lower /regional level and local communities in setting the boundaries. Fourth; Implemention disposition: (1) The occurrence of interest claims resulting disharmony of interests; (2) the existence of public ignorance on the outcomes of the policy. The Supporting factors were: the availability of law products; commitment between government and society; and the lineage similarity of border communities. The inhibiting factors, however, were: minimum budget capacity, very limited availability of infrastructures and lack of coordination. Thus, the proposed suggestions and recommendations were: a necessity for socialization to the public about the purposes and benefits of the policy set; a nnecessity for budget support and other facilities in the border region as a state gateway; a necessity for a clearly distributed tasks and authority,  so that it may not cause sectoral egoism.